Cross-sectional heterogeneity in price-cost margins and the extent of rent sharing at the sector and firm level in France - Sabien Dobbelaere; Jacques Mairesse (Institute for the Study of Labor (IZA), 2005)
This paper studies cross-sectional heterogeneity in price-cost margins and the extent of rent sharing among 48 sectors and 10738 (mainly manufacturing) firms in France. At the sectoral level, the average price-cost mark-up and the average extent of rent sharing amount to 1.701 and 0.368 respectively. Ignoring the occurrence of rent sharing reduces the average price-cost mark-up to 1.500. At the firm level, the average parameters are estimated at 1.814 and 0.558 respectively. Using the Swamy (1970) methodology which corrects the observed heterogeneity for sampling heterogeneity, the corresponding estimates of their robust true dispersion are 0.694 and 0.204. Excluding the existence of rent sharing brings the firm-level average price-cost mark-up down to 1.491. The corresponding robust true dispersion amounts to 0.493.
Keywords: C23; D21; J50; L13; 330; rent sharing; price-cost margins